2010
DOI: 10.3171/2010.3.focus1085
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord traction, vascular compromise, hypoxia, and metabolic derangements in the pathophysiology of tethered cord syndrome

Abstract: Object The definition of tethered cord syndrome (TCS) relies mainly on radiological criteria and clinical picture. The presence of a thickened filum terminale and a low-lying conus medullaris in symptomatic patients is indicative of TCS. The radiological definition of TCS does not take into account cases that involve a normal-lying conus medullaris exhibiting symptoms of the disease. Methods The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…The radicular and medullary arteries and veins will be under tension and thus narrowed with an increase in spinal canal length (flexion) and will be relaxed in the extended posture of the pons-cord tract. 19,54 Mechanically though, it seems logical and is generally accepted that the loss of cervical lordosis is usually accompanied with axial or ventroflexion traction. 25 When the cervical spine is put into flexion, it has been shown that axial rotation increases dramatically, thus putting more torsional strain upon the annuals fibrosis, resulting in possible herniation and excess strain on spinal ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…The radicular and medullary arteries and veins will be under tension and thus narrowed with an increase in spinal canal length (flexion) and will be relaxed in the extended posture of the pons-cord tract. 19,54 Mechanically though, it seems logical and is generally accepted that the loss of cervical lordosis is usually accompanied with axial or ventroflexion traction. 25 When the cervical spine is put into flexion, it has been shown that axial rotation increases dramatically, thus putting more torsional strain upon the annuals fibrosis, resulting in possible herniation and excess strain on spinal ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, the number of compounding comorbidities present increases the risk for postoperative complications, consistent with the multivariate analysis conducted by Lad et al Bui et al 2 summarized the common comorbidities in patients with TCS, which can include cutaneous manifestations, orthopedic abnormalities (i.e., leg-length discrepancy, foot asymmetry, foot deformity, and progressive scoliosis), and urological problems (i.e., neurogenic bladder, incontinence, and frequent urinary 2 Other common comorbidities include degenerative disc disease, spinal stenosis and spondylosis, anorectal abnormalities, split cord malformation, OEIS syndrome (omphalocele, extrophy of the cloaca, imperforate anus, and spinal malformations with TCS), VATER associations, and the Currarino triad (anorectal malformation, presacral mass, and sacral bone abnormalities). 1,3,8,910 To date, no large-scale study has been conducted to determine the prevalence of these comorbid conditions with TCS.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Retethering may produce neurological symptoms through nerve root traction and ischemia or tension distributed through the spinal cord. 3,4,12 We present a case of simple tethered cord due to a fatty filum terminale with 3 distinct episodes of recurrence, each presenting with fecal incontinence and resolving with operative intervention. At the last procedure, a discrete sacral nerve root was recognized and individual nerve roots were separated from the filum before its eventual complete resection.…”
mentioning
confidence: 99%